"A contribution to my country": professional lives of teachers in Timor-Leste. Issue 3 (3rd July 2022) - Quinn, Marie; Buchanan, John
ABSTRACT: International attention to improving learning outcomes has increasingly focused on the impact of teachers, those that directly implement national education goals. For small, resource-poor countries where communities have minimal schooling experience, the role of the teacher in building academic knowledge and skills is even more valued, to both support that community and the nation as a whole. Yet governments and other stakeholders may not know much about their teachers' lives: why they teach, what keeps them motivated and what makes the education system vulnerable to teacher attrition. This paper seeks to understand the lives of the teachers, in this case, in Timor-Leste. This paper reports on the findings from a recent survey of Timorese primary school teachers, finding while the challenges are many, there is a strong sense of personal contribution to the nation's development evident in teachers' work, something that the local education ministry might consider in supporting the work of its teachers.